Deep immune-phenotyping of HLA-homozygous iPS-cardiomyocytes by spectral flow cytometry - Maeding, Nicole; Suresh Kundully, Deepika; Steinhuber, Anna; Kriedemann, Nils; Hernandez-Bautista, Carlos A.; Martins, Soraia; Hochmann, Sarah; Wolf, Martin; Mayr, Wolfgang; Jungbauer, Christof; Diecke, Sebastian; Tonn, Torsten; et al. (Frontiers in Immunology, 2026)
IntroductionImmunogenicity of allogeneic human induced pluripotent stem cell (hiPSC)-derived transplants limits their applicability in regenerative medicine. Selecting human leukocyte antigen (HLA)-homozygous hiPSC lines could be a mitigation strategy and haplo-matching would profoundly expand the number of potential recipients. Here we show deep immune-phenotyping of hiPSC-derived cardiomyocytes (iPS-CM) differentiated from four independent iPSC lines in three centers under chemically defined conditions.Methods and resultsBroad immunophenotyping with 354 antibodies revealed differential expression of 101 immune-related molecules between iPS-CM and the parental hiPSC lines. We selected 54 key immune markers for deep immune-phenotyping by spectral flow cytometry at the single-cell level. We found that HLA-homozygous iPSCMs exhibit an overall stable immune-phenotype across HLA-homozygous and heterozygous hiPSC lines indicating a robust differentiation process. HLA-homozygous iPS-CM displayed significantly reduced HLA-ABC levels compared to heterozygous counterparts with an otherwise conserved immune-phenotype. Upon interferon gamma challenge as a surrogate of immune stress responsiveness, iPS-CM significantly upregulated HLA-ABC, -E, -F, PD-L1, PD-L2 and the 'don't eat me' signal CD47. As a proof-of-concept we used this panel to benchmark iPS-CM differentiation across three production sites in this study.DiscussionThe data indicate generally stable immune-phenotype of iPS-CM produced at three different sites and support feasibility of monitoring iPS-CM identity by spectral flow cytometry.